Exposure to environmental enrichment attenuates addiction-like behavior and alters molecular effects of heroin self-administration in rats. (1st September 2018) - Imperio, Caesar G.; McFalls, Ashley J.; Hadad, Niran; Blanco-Berdugo, Laura; Masser, Dustin R.; Colechio, Elizabeth M.; Coffey, Alissa A.; Bixler, Georgina V.; Stanford, David R.; Vrana, Kent E.; Grigson, Patricia S.; Freeman, Willard M.
Abstract: Environmental factors profoundly affect the addictive potential of drugs of abuse and may also modulate the neuro-anatomical/neuro-chemical impacts of uncontrolled drug use and relapse propensity. This study examined the impact of environmental enrichment on heroin self-administration, addiction-related behaviors, and molecular processes proposed to underlie these behaviors. Male Sprague-Dawley rats in standard and enriched housing conditions intravenously self-administered similar amounts of heroin over 14 days. However, environmental enrichment attenuated progressive ratio, extinction, and reinstatement session responding after 14 days of enforced abstinence. Molecular mechanisms, namely DNA methylation and gene expression, are proposed to underlie abstinence-persistent behaviors. A global reduction in methylation is reported to coincide with addiction, but no differences in total genomic methylation or repeat element methylation were observed in CpG or non-CpG (CH) contexts across the mesolimbic circuitry as assessed by multiple methods including whole genome bisulfite sequencing. Immediate early gene expression associated with drug seeking, taking, and abstinence also were examined. EGR1 and EGR2 were suppressed in mesolimbic regions with heroin-taking and environmental enrichment. Site-specific methylation analysis of EGR1 and EGR2 promoter regions using bisulfite amplicon sequencing (BSAS) revealed hypo-methylation in the EGR2 promoter region and EGR1 intragenic CpG sites with heroin-taking and environmental enrichment that was associated with decreased mRNA expression. Taken together, these findings illuminate the impact of drug taking and environment on the epigenome in a locus and gene-specific manner and highlight the need for positive, alternative rewards in the treatment and prevention of drug addiction. Highlights: Environmental enrichment decreases the reinforcement efficacy of heroin. Genome-wide methylation is not altered in mesolimbic structures with heroin self-administration or environmental enrichment. Gene expression and base-specific methylation responses to heroin are modified by environmental enrichment.